2016
DOI: 10.15621/ijphy/2016/v3i2/94874
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of Emotional Intelligence Training in Physiotherapy Interns a Pilot Study

Abstract: Background: Physiotherapy is a branch of medicine where development of a good rapport between patient and therapist coupled with presence of a caring attitude and emotional understanding of patients would facilitate faster recovery. This study assessed the effect of Emotional Intelligence (EI) training in physiotherapy interns to help them understand their patients better and enhance their self awareness while patient's perceived change in care was examined.Methods: 8 physiotherapy interns completed an EI scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Second, once the company decides to promote PM’s EI, they have several options. There is general evidence that EI can be improved with training (Vishakha Patil and De Sousa, 2016). Companies may invest in the development and implementation of formal EI training programs to strengthen PMs’ competencies, such as short lectures, group discussions, role-play, paired exercises involving the relating and sharing of emotional experiences and one-on-one coaching (Kozlowski et al , 2018; Slaski and Cartwright, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Second, once the company decides to promote PM’s EI, they have several options. There is general evidence that EI can be improved with training (Vishakha Patil and De Sousa, 2016). Companies may invest in the development and implementation of formal EI training programs to strengthen PMs’ competencies, such as short lectures, group discussions, role-play, paired exercises involving the relating and sharing of emotional experiences and one-on-one coaching (Kozlowski et al , 2018; Slaski and Cartwright, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…EI can be enhanced through training programmes. A pilot study conducted among physiotherapy interns reported that statistically significant differences in scores were noted on the EI scale after training (Patil et al, 2016).Interpersonal functioning is a key element in promoting therapistclient relationships in physiotherapy settings. EI training serves as an effective instrument to help physiotherapists understand emotions while helping clients interpret emotional signals (verbal and non-verbal).It will help prevent burnout and emotional exhaustion when attending to clients who cease to respond to physiotherapy or where the hope of recovery is grim (Potter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The disciplines of medicine and dentistry have made attempts to include elements of emotional intelligence in professional education (Cherry, Fletcher, O'Sullivan, & Dornan, 2014;Gorgas, Greenberger, Bahner, & Way, 2015;Munk, 2016). In physiotherapy and paramedicine emotional intelligence training is also being incorporated in pre-clinical education to assist in the development of self-awareness and stress amelioration (Patil, Naik, & De Sousa, 2016;Sellakumar, 2017). Notwithstanding this, there is still uncertainty about whether emotional intelligence influences emotional engagement during clinical placement.…”
Section: The Relationship Between Emotional Labour and Emotional Intementioning
confidence: 99%